ESTUDO DA EVOLUÇÃO MICROESTRUTURAL DO COMPÓSITO METÁLICO USANDO LIGNINAS EXTRAÍDA DA MADEIRA – 2° ETAPA. - Fernandes, Hedielle; Cirilo, Armando; Rossi, Jesualdo; Gouvêa, Adriana; Cardoso, Aline (ANAIS DO ENIC, 2018)
-